Suppression in interpreting adjective noun combinations and the nature of the lexicon. (24th October 2019) - Hogeweg, Lotte
Abstract: A common assumption about our internal lexicon is that the meaning of words is underspecified and this underspecified representation is filled in based on the context in which the word occurs. In this paper I would like to explore a different hypothesis, that words are stored with overspecified representations which are 'trimmed down' by the context. This view seems to be in line with a well-known mechanism from psycholinguistics: suppression. Many studies have shown that conceptual properties of a word are initially activated but subsequently suppressed when these properties are in conflict with the context the word occurs in. This mechanism has not been tested, however, in a context where compositional application takes place as between an adjective and a noun. In this study I will discuss two lexical decision experiments testing the interpretation of two types of adjective noun combinations. For both types of combinations it is expected that the representation of the noun undergoes a change due to the conflicting information provided by the adjective. It is hypothesized that the properties of the noun that are in conflict with the adjective are initially activated, but subsequently suppressed to form a coherent representation of the adjective noun combination. While the results provide evidence for the initial activation of the conceptual properties, no evidence for the subsequent suppression was found. The initial activation shows that also in the case of adjective noun combinations, conceptual features do not 'wait for' an initial well-formed semantic structure. The lack of evidence for suppression primarily suggests the need for further research. If future experiments confirm that suppression does not take place within the time frame tested in the experiments, we must conclude, based on experimental findings by Schumacher (2013 ), that conceptual specification takes place after the shift in reference of the noun.